The Effect of Liquidity, Activitiy and Capital Structure on Profitability, Financial Distress and Firm Value in Building Construction and Property and Real Estate Companies Listed on The Indonesia Stock Exchange - Kurniawati, Dinda Dwi; Ratnawati, Tri; Pristiana, Ulfi (International Journal of Economics (IJEC), 2024)
This study aims to analyze the effect of liquidity, activity and capital structure on profitability, financial distress and firm value in building construction and property and real estate companies listed on the Indonesia stock exchange. The population in the study were building construction and property and real estate companies listed on the Indonesia stock exchange in 2018-2022. 17 companies were selected as samples using saturated samples. Hypothesis testing in this study was carried out with the smrart-PLS application. Based on the analysis of 11 hypotheses, it was found that liquidity has no significant effect on profitability, financial distress and firm value. Activity has a significant effect on financial distress and firm value but activity has no significant effect on profitability. Capital structure has a significant effect on financial distress and firm value but capital structure has no significant effect on profitability. Profitability and financial distress have no significant effect on firm value. Liquidity, activity and capital structure have no significant effect on firm value through profitability as an intervening variable. Liquidity, activity and capital structure have no significant effect on firm value through financial distress as an intervening variable.